SOSIALISASI EFEKTIVITAS PENGAJARAN DALAM MENDUKUNG PEMENUHAN BEBAN KERJA DOSEN DI POLITEKNIK PENERBANGAN INDONESIA CURUG - H, Megi Hudi; W, Rinosa Ari; fatonah, Feti; D, Nurhedhi; Kurnianingsih, Lilis; W, Dody Wahyu; P, Triyani Retno; Kartika, Dian (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service activity aims to provide understanding to lecturers and prospective lecturers, especially in the Aviation study program. This is necessary because there are many prospective lecturers who currently still have the status of Flight Instructors who want to know and understand about the calculation of teaching hours in fulfilling the Lecturer BKD. This socialization activity discusses the calculation of teaching hours and how to apply the calculation of teaching hours into the system according to the BKD rubric guide. In addition to this, this activity also provides an understanding of the need for teaching hours in fulfilling the BKD in one semester